The improvement properties of steel fibre reinforced geopolymer concrete - Meor Ahmad Faris Meor Ahmad Tajudin (School of Materials Engineering, 2019)
The research objectives for this studies are summarized as bellow; to determine optimum percentage of steel fibres addition in fly ash geopolymer concrete based on physical and mechanical properties; to identify the effects on different types of steel fibres addition in fly ash geopolymer concrete based on physical and mechanical properties; to investigate the fibre-geopolymer matrix interfacial behaviour of steel fibre reinforced geopolymer concrete.